Ocean Glacial Arctique, Iénisséï / d'après les levés du Général Vilkidski et les observations de M. Hulin - France. Service hydrographique de la marine (1920)
Relief shown by hachures and spot heights. Depths shown by soundings.; Includes key to segments and four inset views Color;